Transatlantic progress in measurement of cognitive outcomes in paediatric oncology trials. Issue 5 (3rd February 2023) - Thomas, Sophie; Embry, Leanne; Walsh, Karin; Bull, Kim; Grundy, Richard; Kennedy, Colin; Lemiere, Jurgen; Hernáiz Driever, Pablo; Limond, Jennifer; Chevignard, Mathilde; Hardy, Kristina
Abstract: The importance of measuring quality of survival within paediatric oncology trials is increasingly recognised. However, capturing neuropsychological outcomes and other aspects of quality of survival in the context of large or multinational trials can be challenging. We provide examples of protocols designed to address this challenge recently employed in clinical trials in the USA and Europe. We discuss their respective strengths and challenges, obstacles encountered and future opportunities for transatlantic collaboration.